2011
DOI: 10.1016/j.joca.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

T helper cells promote disease progression of osteoarthritis by inducing macrophage inflammatory protein-1γ

Abstract: CD4(+) T cells were activated during the onset of OA, but cartilage damage was more prominent at a later stage. CD4(+) T cells were involved in the pathogenesis of OA: they induced MIP-1γ expression and subsequent osteoclast formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 28 publications
5
82
1
Order By: Relevance
“…A possible mechanism is the elevated MMP-9 secretion induced by higher IL-6 expression from monocytes, which is activated by the synovial inflammatory response, thereby disturbing the balance between MMPs and TIMPs and leading to the damage of chondrocytes (Guo et al, 2011). In this process, IL-6 stimulates the production of prostaglandin and collagenase in normal cartilage and synovial cells in order to stimulate the IL-1 induced-MMP response in synovial fibroblasts in rheumatoid arthritis (Litinsky et al, 2006;Wang et al, 2010;Shen et al, 2011) or to elevate the expression of VEGF (vascular endothelial growth factor) type II receptor, thus facilitating MMP-9 secretion (Sakao et al, 2008;Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism is the elevated MMP-9 secretion induced by higher IL-6 expression from monocytes, which is activated by the synovial inflammatory response, thereby disturbing the balance between MMPs and TIMPs and leading to the damage of chondrocytes (Guo et al, 2011). In this process, IL-6 stimulates the production of prostaglandin and collagenase in normal cartilage and synovial cells in order to stimulate the IL-1 induced-MMP response in synovial fibroblasts in rheumatoid arthritis (Litinsky et al, 2006;Wang et al, 2010;Shen et al, 2011) or to elevate the expression of VEGF (vascular endothelial growth factor) type II receptor, thus facilitating MMP-9 secretion (Sakao et al, 2008;Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response occurring in the synovial membrane of osteoarthritic patients exhibits features of a T cell immune response [23]. It has been reported that CD3 positive T cells infiltrate in the synovium of osteoarthritic patients [24] and T helper cells promote disease progression of osteoarthritis [25]. Therefore, an antigen-driven immune response exists in osteoarthritic patients.…”
Section: Discussionmentioning
confidence: 99%
“…CD4(+) T cells promote disease progression of OA by inducing macrophage inflammatory protein-1γ. CD4(+) T cells (express the CD4 protein on their surface) are activated during the onset of OA and cause marked damage to cartilage at a later stage (34).…”
Section: Discussionmentioning
confidence: 99%